Targeted control over the porosities and functionalities of conjugated microporous polycarbazole networks for CO2-selective capture and H2 storage. Issue 46 (15th November 2017) - Liao, Yaozu; Cheng, Zhonghua; Trunk, Matthias; Thomas, Arne
Abstract : Target controllable conjugated microporous polycarbazole networks with pyridine-, bipyridine-, and cyano-functionalized networks exhibit a large surface area and tunable gas uptake. Abstract : We report a conjugated microporous polycarbazole network and its pyridine-, bipyridine-, and cyano-functionalized networks exhibiting large surface area (1126 m 2 g −1 ), isosteric heat of CO2 adsorption (∼32 kJ mol −1 ), and CO2 -uptake capacity (14 wt% at 1 bar and 273 K). IAST calculations using single-component-isotherms reveal that the functionalized polycarbazole networks have a very high CO2 selectivity over N2 (164) under ambient conditions. These porous networks also possess moderate H2 storage capacity (1.35 wt% at 1 bar and 77 K) and high isosteric heat of H2 adsorption (10.3 kJ mol −1 ). Our finding provides a new targeted route to control the porosities and functionalities of microporous polymers for efficient gas uptake.